Serum/Synovial Fluid Urate Ratio as an Indicator for Distinguishing Gouty Arthritis From Other Arthritides - Shunfei LU,; Qiankun ZHANG,; Yan ZHOU, (Archives of Rheumatology, 2019)
Objectives: This study aims to compare the serum/synovial fluid (SF) urate ratio of gouty arthritis and other arthritides and investigate whether this ratio may be an indicator for distinguishing gouty arthritis from other arthritides. Patients and methods: Paired serum and SF samples from 70 patients (38 males, 32 females; mean age 57.9 years; range, 27.5 to 78.4 years) comprised of 20 patients with gout, 20 patients with rheumatoid arthritis and 30 patients with osteoarthritis were collected simultaneously for urate measurement. Patient data were recorded including demographic data (age, sex), body mass index, estimated glomerular filtration rate, comorbidities (diabetes, hypertension and dyslipidemia), disease duration (from the first symptoms), pain duration before arthrocentesis at this time, presence of tophi or not, serum albumin, erythrocyte sedimentation rate, C-reactive protein and SF white blood cell count. Results: Gout patients had highest levels of urate in both serum and SF among the three groups (p<0.001). The serum/SF urate ratio of gout patients was significantly lower among the three groups (p<0.001). Receiver-operating characteristic curve analysis demonstrated that serum/SF urate ratio can predict the extent of gouty arthritis (the value of area under the curve was 0.867, p<0.001). Conclusion: Serum/SF urate ratio may be an indicator for distinguishing gouty arthritis from other arthritides.